2015
DOI: 10.1111/jcpp.12435
|View full text |Cite
|
Sign up to set email alerts
|

Research Review: Use of EEG biomarkers in child psychiatry research – current state and future directions

Abstract: Background Electroencephalography (EEG) and related measures have a long and productive history in child psychopathology research and are currently experiencing a renaissance in interest, particularly for use as putative biomarkers. Method and Scope First, the recent history leading to the use of EEG measures as endophenotypes and biomarkers for disease and treatment response are reviewed. Two key controversies within the area of non-invasive human electrophysiology research are discussed, and problems that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
76
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(79 citation statements)
references
References 63 publications
(76 reference statements)
1
76
1
1
Order By: Relevance
“…Collectively, these findings indicate that an abnormal Pe and differences in Go/No-go N2 waveform amplitudes may be potential endophenotypes signaling developing psychopathology and risk for myriad negative outcomes. The burgeoning interest in ERPs as clinical endophenotypes of psychiatric risk has, to date, largely focused on the ERN and risk for anxiety, depression, and substance abuse in older populations, as opposed to early onset externalizing psychopathology (Euser et al, 2013; Iacono & Malone, 2011; Loo et al, 2016). More recent studies showed that the ERN, Pe, and No-go N2 are rank stable over a 1 to 2 year period in child and adolescent populations (Burwell, Malone, & Iacono, 2016; Meyer, Bress, & Proudfit, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Collectively, these findings indicate that an abnormal Pe and differences in Go/No-go N2 waveform amplitudes may be potential endophenotypes signaling developing psychopathology and risk for myriad negative outcomes. The burgeoning interest in ERPs as clinical endophenotypes of psychiatric risk has, to date, largely focused on the ERN and risk for anxiety, depression, and substance abuse in older populations, as opposed to early onset externalizing psychopathology (Euser et al, 2013; Iacono & Malone, 2011; Loo et al, 2016). More recent studies showed that the ERN, Pe, and No-go N2 are rank stable over a 1 to 2 year period in child and adolescent populations (Burwell, Malone, & Iacono, 2016; Meyer, Bress, & Proudfit, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Event Related Potentials (ERPs), electroencephalographic (EEG) waveforms time-locked to specific cognitive or emotional events (Luck, 2014), may significantly advance our understanding of dysregulated processes that underpin early disruptive behavior. In early childhood, high disruptive behavior may be associated with abnormal neuro-electrical waveforms at the onset of specific self-regulation demands, representing potential endophenotypes of future risk (Euser, Evans, Greaves-Lord, Huizink, & Franken, 2013; Loo, Lenartowicz, & Makeig, 2016). However, to our knowledge, there are no studies comparing self-regulation-related ERPs in preschoolers with and without high levels of disruptive behavior.…”
mentioning
confidence: 99%
“…Many thoughtful endophenotype articles populate the literature (for recent examples, see Anokhin, 2014; Beauchaine, 2009; Burton et al, 2015; Campanella, Pogarell, & Boutros, 2014; Euser et al, 2012; Faraone, Bonvicini, & Scassellati, 2014; Ferrarelli, 2013; Glahn et al, 2014; Goldstein & Klein, 2014; W. G. Iacono & Malone, 2011; Lenzenweger, 2013; Loo, Lenartowicz, & Makeig, 2015; Manoach & Agam, 2013; Miller & Rockstroh, 2013; Moses-Kolko, Horner, Phillips, Hipwell, & Swain, 2014; Owens, Bachman, Glahn, & Bearden, 2016; Pearlson, 2015; Rosen, Spellman, & Gordon, 2015; Rubenstein, Wiggins, & Lee, 2015; Salvatore, Gottesman, & Dick, 2015; Swerdlow, Gur, & Braff, 2015), and many of these share a conviction that endophenotypes are valuable for identifying genetic liability . However, despite their introduction to psychiatry by Gottesman and Shields (I.…”
Section: 0 Introductionmentioning
confidence: 99%
“…Indeed, a recent review demonstrated that using unmixed signals from source-resolved analyses can be more powerful in unmasking clinical group differences (Loo et al, 2015; Stewart et al, 2010). Importantly, recent research in psychopathology and behavior has begun to move in the direction of source-localization to clarify the functional role of these brain processes (e.g., Auerbach et al, 2015; Schiller et al, 2014).…”
Section: Introductionmentioning
confidence: 99%